The Anti‐Depressive Effects of Ultra‐High Static Magnetic Field. Issue 2 (18th December 2021) - Lv, Yue; Fan, Yixiang; Tian, Xiaofei; Yu, Biao; Song, Chao; Feng, Chuanlin; Zhang, Lei; Ji, Xinmiao; Zablotskii, Vitalii; Zhang, Xin
Abstract : Background: Ultra‐high field magnetic resonance imaging (MRI) has obvious advantages in acquiring high‐resolution images. 7 T MRI has been clinically approved and 21.1 T MRI has also been tested on rodents. Purpose: To examine the effects of ultra‐high field on mice behavior and neuron activity. Study Type: Prospective, animal model. Animal Model: Ninety‐eight healthy C57BL/6 mice and 18 depression model mice. Field Strength: 11.1–33.0 T SMF (static magnetic field) for 1 hour and 7 T for 8 hours. Gradients were not on and no imaging sequence was used. Assessment: Open field test, elevated plus maze, three‐chambered social test, Morris water maze, tail suspension test, sucrose preference test, blood routine, biochemistry examinations, enzyme‐linked immunosorbent assay, immunofluorescent assay. Statistical Tests: The normality of the data was assessed by Shapiro–Wilk test, followed by Student's t test or the Mann–Whitney U test for statistical significance. The statistical cut‐off line is P  < 0.05. Results: Compared to the sham group, healthy C57/6 mice spent more time in the center area (35.12 ± 4.034, increased by 47.19%) in open field test and improved novel index (0.6201 ± 0.02522, increased by 16.76%) in three‐chambered social test a few weeks after 1 hour 11.1–33.0 T SMF exposure. 7 T SMF exposure for 8 hours alleviated the depression state of depression mice, including less immobile time in tail suspension test (58.32% reduction) and higher sucrose preference (increased by 8.80%). Brain tissue analysis shows that 11.1–33.0 T and 7 T SMFs can increase oxytocin by 164.65% and 36.03%, respectively. Moreover, the c‐Fos level in hippocampus region was increased by 14.79%. Data Conclusion: 11.1–33.0 T SMFs exposure for 1 hour or 7 T SMF exposure for 8 hours did not have detrimental effects on healthy or depressed mice. Instead, these ultra‐high field SMFs have anti‐depressive potentials. Evidence Level: 1 Technical Efficacy: Stage 1